Association between vitamin D level in mother's serum and the level of vitamin D in the serum of pre-term infants - Alireza Jashni Motlagh; Ahmadreza Davoodvandi; Sara Esmaelzadeh Saeieh (BMC, 2023)
Abstract Background Vitamin D deficiency and insufficiency is common in mothers and infants. The present study was conducted with the aim of association between the level of vitamin D in the mother's serum and the level of vitamin D in the serum of preterm infants. Method The present descriptive - analytical study was performed on 140 mothers and preterm infants referred to the Kamali hospital in Alborz University of Medical Sciences. Sampling was done from available mothers after hospitalization for delivery and their infants during the first 72 hours after delivery. Information from mothers and infants were collected with researcher made check list, including age, type of delivery, number of pregnancies, vitamin D during this pregnancy, infants birth age, gender, and birth weight. Data analysis was performed using SPSS version 24 software. Results The average age of mothers was 28 ± 5 years and the average age of infants at the time of birth was 30 ± 1 weeks. Forty two infants (67%) were boys and 23 infants (33%) were girls. The results showed a high rate of vitamin D insufficiency and deficiency in mother (44, 49%) and preterm infants (49, 38%). The results of the Pearson correlation test showed that there is a strong and significant relationship between the serum vitamin D level of mothers and preterm infants (P = 0.001). Logistic regression tests showed that mother's vitamin D level had an effect on the infant's vitamin D level. Conclusion Considering high rate of vitamin D deficiency and insufficiency and relationship between vitamin D in preterm infants serum and mothers, diagnostic screenings are recommended to investigate vitamin D disorders in pregnant mothers, which should be planned, implemented and followed up in the form of a therapeutic program to prevent the occurrence of complications caused by this disorder in the mother and infant.